2022
DOI: 10.1021/acs.macromol.2c00907
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Controls Nanoparticle Size during Nanoprecipitation by Limiting Block Copolymer Assembly

Abstract: Control of the properties of nanoparticles (NPs), including size, is critical for their application in biomedicine and engineering. Polymeric NPs are commonly produced by nanoprecipitation, where a solvent containing a block copolymer is mixed rapidly with a nonsolvent, such as water. Empirical evidence suggests that the choice of solvent influences NP size; yet, the specific mechanism remains unclear. Here, we show that solvent controls NP size by limiting block copolymer assembly. In the initial stages of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…Interestingly, it has been proposed in the literature that the presence of solvent, monomer or molecules with similar chemical structure may help morphological transitions. [44][45][46][47][48][49][50] On the one hand, we have demonstrated that the presence of toluene in a typical emulsion polymerization of styrene via PISA has a great impact on the morphologies formed; [50] on the other hand, the addition of plasticizing solvents postpolymerization (to particles obtained by PISA or mini-or nanoemulsion) was extensively explored by the groups of Davis [44] and Anastasaki. [45] For instance, the latter showed that the addition of toluene in an aqueous dispersion of nano-objects comprising a polystyrene solvophobic block can trigger quick transitions toward higher order morphologies.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Interestingly, it has been proposed in the literature that the presence of solvent, monomer or molecules with similar chemical structure may help morphological transitions. [44][45][46][47][48][49][50] On the one hand, we have demonstrated that the presence of toluene in a typical emulsion polymerization of styrene via PISA has a great impact on the morphologies formed; [50] on the other hand, the addition of plasticizing solvents postpolymerization (to particles obtained by PISA or mini-or nanoemulsion) was extensively explored by the groups of Davis [44] and Anastasaki. [45] For instance, the latter showed that the addition of toluene in an aqueous dispersion of nano-objects comprising a polystyrene solvophobic block can trigger quick transitions toward higher order morphologies.…”
Section: Zuschriftenmentioning
confidence: 99%
“…The dynamics of the polymer chains is also maximal at the beginning of the dialysis when the THF fraction is high. 18,20,45 Both these conditions probably favor the early BC self-assembly into vesicles following a different pathway among the multiple metastable states that can exist in the free energy landscape of a BC system. 19,46,47 Modifying the membrane porosity is therefore a simple way to perform self-assembly under kinetic or thermodynamic control which can be of interest for many polymer and colloidal systems.…”
Section: Figurementioning
confidence: 99%
“…16,17 A recurring issue with the solvent exchange method is the equilibrium state of BC aggregates, which depends not only on the final water content but also on the magnitude and rate of the water jump. 14,[18][19][20] In order to promote the formation of equilibrium morphologies, as expected for phase diagrams, water should be added slowly and gradually, by analogy with the conditions used for annealing in bulk studies. 21 A fast and large water jump can lead to kinetically arrested morphologies, which is the basis to form BC nanoparticles by the so-called flash nanoprecipitation technique.…”
mentioning
confidence: 99%
“…Interestingly, it has been proposed in the literature that the presence of solvent, monomer or molecules with similar chemical structure may help morphological transitions. [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ] On the one hand, we have demonstrated that the presence of toluene in a typical emulsion polymerization of styrene via PISA has a great impact on the morphologies formed; [50] on the other hand, the addition of plasticizing solvents post‐polymerization (to particles obtained by PISA or mini‐ or nanoemulsion) was extensively explored by the groups of Davis [44] and Anastasaki. [45] For instance, the latter showed that the addition of toluene in an aqueous dispersion of nano‐objects comprising a polystyrene solvophobic block can trigger quick transitions toward higher order morphologies.…”
mentioning
confidence: 99%